Implementing Multi-Access Edge Computing with Kubernetes - Kjorveziroski, Vojdan; Bernad Canto, Cristina; Gilly, Katja; Filiposka, Sonja (ICT Innovations, 2022)
The introduction of novel telecommunication standards such as 5G and beyond, which offer increased throughput and more efficient network communication, serve as enablers for new technologies. One of these technologies is Multi-Access Edge Computing (MEC), with the potential to revolutionize existing computing architectures and their feature set as we know them to-day. By collocating compute nodes with mobile networking equipment, customers are offered reduced latency and increased privacy, compared to alternative scenarios where the traffic is indiscriminately routed to the cloud. However, the distributed nature of the mobile landscape, coupled with the huge number of involved parties, requires careful consideration and standardization before any rollout. A number of reference documents have been published in recent years with the aim of standardizing the communication interfaces of MEC. We discuss these standardization efforts and provide a description of a MEC architecture centered around the Kubernetes container orchestrator, replacing the concept of virtualized MEC applications with containerized instances which can be deployed as serverless functions. We also offer a use-case scenario leveraging the described component mapping, showcasing the scalability and load-balancing features of the proposed architecture.
Keywords: Multi-Access Edge Computing, Architecture Mapping, Kubernetes, Serverless Computing, 5G.